2007
DOI: 10.1111/j.1468-5930.2007.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Killing and Letting Die: the Similarity Criterion

Abstract: Applied ethics engages with concrete moral issues. This engagement involves the application of philosophical tools. When the philosophical tools used in applied ethics are problematic, conclusions about applied problems can become skewed. In this paper, I focus on problems with the idea that comparison cases must be exactly alike, except for the moral issue at hand. I argue that this idea has skewed the debate regarding the moral distinction between killing and letting die. I begin with problems that can arise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
0
8
0
Order By: Relevance
“…aspects (a), (b), (c), (d) and (f) also obtain in context E. 40 Arguably, these connotations or nuances of meaning and context are not factors extraneous to the issue of the killing / letting die distinction; they are partially constitutive of the meaning of those expressions in the context that is relevant to the debate about WLT and VAE (59). 41 Note that we do not claim that (a) through (f) exhaust the ethically relevant aspects unique to the clinical situation that might encompass contexts W and E.…”
Section: Negative Examples: the Tendency To Irrelevant Abstractionsmentioning
confidence: 94%
“…aspects (a), (b), (c), (d) and (f) also obtain in context E. 40 Arguably, these connotations or nuances of meaning and context are not factors extraneous to the issue of the killing / letting die distinction; they are partially constitutive of the meaning of those expressions in the context that is relevant to the debate about WLT and VAE (59). 41 Note that we do not claim that (a) through (f) exhaust the ethically relevant aspects unique to the clinical situation that might encompass contexts W and E.…”
Section: Negative Examples: the Tendency To Irrelevant Abstractionsmentioning
confidence: 94%
“…The distinction between active and passive benefits can be viewed as a special case of the distinction between 'doing' and 'allowing'. Many philosophers have debated the nature and validity of this distinction (Asscher 2007;Bennett 2003;Bradley and Stocker 2005). Studies in experimental philosophy have demonstrated that lay people distinguish between situations of 'doing harm' and 'allowing harm', and attribute greater compensatory responsibility to 'doing harm' cases than to 'allowing harm' cases (Barry et al 2014).…”
Section: Effects Of Activity On Ethical and Legal Judgmentsmentioning
confidence: 99%
“…A whole proposition cannot be true without its parts being true, but each part can be true without the whole being true. 3 Likewise, a whole property cannot be instantiated without its parts being instantiated, and a whole state of affairs cannot obtain without its parts obtaining.…”
Section: Introductionmentioning
confidence: 99%
“…So the parts of a song, though abstract, seem nonetheless complete. 3 Sometimes propositions are said to have parts, or "constituents", of another sort. For example, the proposition that Papalymo is a bachelor might be said to have the individual Papalymo and the property of being a bachelor as parts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation